DIFFERENCES BETWEEN TABOOS AND STEREOTYPES ACROSS COUNTRIES: A CROSS-CULTURAL ANALYSIS - Mengto'rayeva Shodiya Hamidulla qizi; Xudoyberdiyeva Laylo Abdumalik Qizi; Qurbonova Gulzira Olimovna (TADQIQOTLAR, 2025)
Taboos and stereotypes are integral components of cultural frameworks that shape social interactions and perceptions worldwide. While taboos represent prohibitions rooted in cultural, religious, or moral beliefs, stereotypes are generalized assumptions about groups based on perceived characteristics. This article examines the distinctions between taboos and stereotypes, their manifestations across various countries, and their implications for intercultural communication. Using a comparative approach, we analyze examples from diverse cultural contexts, including China, India, the United States, and Saudi Arabia, to highlight how these phenomena influence behavior and societal norms. The findings underscore the importance of cultural sensitivity in navigating global interactions and suggest strategies for fostering mutual understanding.